Trends and inequalities of minimum dietary diversity among children aged 6–23 months in Sierra Leone, 2013–2019 - Augustus Osborne; Camilla Bangura; Umaru Sesay (BMC Public Health)
Abstract Background Ensuring a healthy and diverse diet for young children is crucial for their proper growth and development. This study examined the trends and inequalities in minimum dietary diversity in Sierra Leone between 2013 and 2019, focusing on children aged 6–23 months. Methods The study employed a time-trend ecological study design utilising the Sierra Leone Demographic Health Survey data rounds (2013 and 2019). The World Health Organization health equity assessment toolkit software was used to calculate both simple difference (D) and ratio (R) and complex measures of inequality: population attributable risk (PAR) and population attributable fraction (PAF). The inequality assessment was done for six stratifiers: child’s age, household wealth quintile, maternal level of education, place of residence, sex of the child, and sub-national province. Results Minimum dietary diversity among children aged 6–23 months in Sierra Leone increased from 13.4% in 2013 to 25.1% in 2019. Household economic inequality between children from richest households and those from poorest households decreased from 16.2% in 2013 to 8.3% in 2019. Inequality for place of residence between children of mothers in urban areas, and those from rural areas decreased from 8.8% in 2013 to 3.7% in 2019. For child's sex, the inequality between male and female children decreased from − 2.1% in 2013 to -3.7% in 2019. However, inequalities in child’s age, maternal education and sub-national province increased over time, the absolute differences between the groups increased, from 12.6% in 2013 to 20.3% in 2019 between children aged 18–23 months and those aged 6-8 months. Also, from 12.4% in 2013 to 20.6% in 2019 between children of mothers with higher and those with no education and from 18.2% in 2013 to 21.3% in 2019 between children of mothers residing in Western area and those in the Eastern province. Conclusion While the trend in minimum dietary diversity among children aged 6–23 months has shown an encouraging increase between 2013 and 2019, the proportion in 2019 indicates that further efforts are needed to improve minimum dietary diversity. Decreasing inequalities related to economic status, place of residence, and sex is promising, reflecting the country's progress toward achieving universal health coverage by 2030. However, the rise in age-related, educational and provincial inequalities, with children aged 6–8 months, those from less educated households and those in the eastern province disproportionately affected, is concerning. This highlights the need for targeted interventions to improve minimum dietary diversity among these groups. The government and policymakers in Sierra Leone should continue efforts to ensure all families, regardless of age, economic, educational or provincial background, have access to resources and information for child nutrition.